The Making of Might-Have-Beens: Effects of Free Will Belief on Counterfactual Thinking. (February 2015) - Alquist, Jessica L.; Ainsworth, Sarah E.; Baumeister, Roy F.; Daly, Michael; Stillman, Tyler F.
Counterfactual thoughts are based on the assumption that one situation could result in multiple possible outcomes. This assumption underlies most theories of free will and contradicts deterministic views that there is only one possible outcome of any situation. Three studies tested the hypothesis that stronger belief in free will would lead to more counterfactual thinking. Experimental manipulations (Studies 1-2) and a measure (Studies 3-4) of belief in free will were linked to increased counterfactual thinking in response to autobiographical (Studies 1, 3, and 4) and hypothetical (Study 2) events. Belief in free will also predicted the kind of counterfactuals generated. Belief in free will was associated with an increase in the generation of self and upward counterfactuals, which have been shown to be particularly useful for learning. These findings fit the view that belief in free will is promoted by societies because it facilitates learning and culturally valued change.